The last picture show [videorecording (DVD)] - Bogdanovich, Peter, 1939-; McMurtry, Larry; Bridges, Jeff, 1949-; Burstyn, Ellen, 1932-; Shepherd, Cybill, 1950-; Leachman, Cloris; Bouzereau, Laurent (Columbia TriStar Home Video, 1999)
A bittersweet drama of the social and sexual mores in small-town 1950s Texas.